2008
DOI: 10.1007/s10826-008-9223-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Family Environment, Parenting Practices, and Executive Functioning of Children with and Without ADHD

Abstract: We examined the relationships between executive functioning, family environment, and parenting practices in children diagnosed with ADHD as compared to children without ADHD. Participants were parents (N = 134) of 6-to 12-year-old ADHD and non-ADHDdiagnosed children. Compared to the control group, parents of children diagnosed with ADHD reported their children as exhibiting greater problems with behavioral control and metacognitive abilities, and described their family environments as less organized and higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 32 publications
(43 reference statements)
7
55
1
8
Order By: Relevance
“…Compared with the many prior research (Parke, et al, 1992;Thompson, 1994, Nixon and Watson 2001, Chen et al, 2005, McLaughlin, et al 2007, Scheroeder & Kelley 2009) the home environment was not found as a significant predictor of children's emotional intelligence in the study. Consistent with this result Schimitz (2006) indicated that home environment was not predictive of child global self-esteem.…”
Section: Discussioncontrasting
confidence: 97%
“…Compared with the many prior research (Parke, et al, 1992;Thompson, 1994, Nixon and Watson 2001, Chen et al, 2005, McLaughlin, et al 2007, Scheroeder & Kelley 2009) the home environment was not found as a significant predictor of children's emotional intelligence in the study. Consistent with this result Schimitz (2006) indicated that home environment was not predictive of child global self-esteem.…”
Section: Discussioncontrasting
confidence: 97%
“…In particular, parents of adolescents with ADHD describe their family environments as being less organized and structured and having significantly greater family conflict in comparison to parents of adolescents without ADHD (Deault 2010;Schroeder and Kelley 2009). Moreover, parents of adolescents with ADHD are less likely to provide consistent and clear structure surrounding house-rules and routines such as bedtime (Deault 2010), and as reviewed above, adolescents without consistent parent-set bedtimes obtain less sleep and have greater daytime sleepiness than adolescents with parent-set bedtimes (National Sleep Foundation 2006;Noble et al 2012;Short et al 2011).…”
Section: Example Psychosocial Factorsmentioning
confidence: 99%
“…The pressure for succeeding in school has been increased among children compared to the past 2,6 . They are challenging themselves with increased stress on education and self-control.…”
Section: Results A) Children and Mental Healthmentioning
confidence: 99%
“…Those demands cause stress in children's lives and affects their performances' evaluation processes. High stress level negatively influences children's health, and could cause anxiety, insomnia, hypertension, and muscle pain, as well as damages to their immune system 5,6 . Previous researches supported that stress also could lead to heart disease, depression, and overweight or even to compromises to general health [7][8][9] .…”
mentioning
confidence: 99%